2022 Kansas State University Industrial Hemp Dual-Purpose Variety Trials - Kraig Roozeboom; Jason Griffin (Kansas Agricultural Experiment Station Research Reports, 2023)
Hemp is a broad term used to describe the many varieties ofCannabis sativaL. that produce less than 0.3% tetrahydrocannabinol (THC). The crop is globally significant and has recently been approved in the United States. There are many uses for industrial hemp, and the market for industrial hemp is rapidly growing as more states are legalizing its production. Industrial hemp is marketed for oil, grain, and fiber. Varieties have been selected for improved fiber and grain production that can service these markets. However, little research-based information is available regarding adaptability or production of these varieties in Kansas. The objectives of this research were to evaluate commercially available varieties of industrial hemp at two locations in Kansas.
Keywords: hemp; varieties; fiber; grain; dual-purpose